The Well-Being of Young Canadian Children in International Perspective - Shelley Phipps (Luxembourg Income Study (LIS), 1999)
The goal of this paper is to compare the well-being of young children in Canada, Norway and the United States. Many economic models focus on children's eventual well-being by adopting an investment perspective. While this is important, children's well-being today should also count when we assess social welfare - after-all, children constitute nearly one quarter of the Canadian population. To assess the well-being of young children, Sen's (1992) 'functionings' perspective is employed. While income is a vital input to well-being, it is probably not the best measure, particularly of children's well-being. Yet, lack of suitable data has meant that little cross-national evidence about indicators of children's well-being beyond income exists. The principal goal of this paper is to begin to fill this gap. We compare children cross-nationally in terms of ten 'functionings' (low-birth-weight; asthma; accidents; activity limitation; trouble concentrating; disobedience at school; bullying; anxiety; lying; hyperactivity). Results indicate that young children in Norway are better off than children in Canada or the US. It is not clear whether young children are, on average, better off in Canada or the US. However, children at the bottom of the Canadian income distribution are more likely to be better off than children at the bottom of the US income distribution.
Keywords: 330; Lebensstandard; Soziale Lage; Kinder; Kanada; Norwegen; USA